2000
DOI: 10.1080/00016340009169245
|View full text |Cite
|
Sign up to set email alerts
|

High-density vaginal Ureaplasma urealyticum colonization as a risk factor for chorioamnionitis and preterm delivery

Abstract: Acta Obstet Gynecol Scand 2000; 79: 973-978. C Acta Obstet Gynecol Scand 2000Background. The aim of this case control study was to investigate the influence of genital Ureaplasma urealyticum colonization on pregnancy outcome. Methods. One hundred and seventy-two women colonized with Ureaplasma urealyticum without co-existing other infections and 123 women with negative cultures for Ureaplasma urealyticum were enrolled. In a multivariate analysis the influence of quantitative Ureaplasma urealyticum colonization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 13 publications
0
25
0
2
Order By: Relevance
“…spp., resulting in a very high Ureaplasma load. Indications that the number of colonizing organisms could be important when looking for risk factors for preterm birth was found by some authors (16,18). They found heavy growth of mycoplasmas or U. spp.…”
Section: Discussionmentioning
confidence: 99%
“…spp., resulting in a very high Ureaplasma load. Indications that the number of colonizing organisms could be important when looking for risk factors for preterm birth was found by some authors (16,18). They found heavy growth of mycoplasmas or U. spp.…”
Section: Discussionmentioning
confidence: 99%
“…One contributing factor for this new BPD was reported to be perinatal infection including CAM 16–18 . Several studies reported that genital or placental colonization of U. urealyticum was associated with CAM 5,19–21 . Watterberg et al reported that infants born after CAM had decreased risk of respiratory distress syndrome (RDS) but increased risk of CLD compared with the controls 22 .…”
mentioning
confidence: 99%
“…Isolation of Ureaplasma parvum/urealyticum from the placenta is consistently correlated with disease when histologic evidence of chorioamnionitis is used as the criterion, 1,[8][9][10][11][12][13][14][15][16] and adverse pregnancy outcomes (APO), including fetal infection have been correlated with the numbers of U urealyticum isolated from reproductive sites during pregnancy. 17 Importantly, antenatal intrauterine infection with ureaplasmas also has been linked to severe pulmonary and neurologic disorders in neonates. 2,7,9,18,19 Mycoplasma pulmonis genital disease is the only naturally occurring reproductive disease in laboratory animals that is caused by a member of the class Mollicutes, and infection of the uterus can be accomplished by both intravaginal and intravenous (IV) routes.…”
mentioning
confidence: 99%